Characteristics of NOM Released to Water from Different Forest and Agricultural Soils - Hongjie Gui; Fusheng Li; Yongfen Wei; Toshiro Yamada; Reni Desmiarti (Journal of Engineering and Technological Sciences, 2016)
The characteristics of natural organic matter (NOM) released to water from a soil environment were investigated based on the release potential and the quality indexes of SUVA, fluorescence EEM and molecular weight distribution using eight forest and agricultural soils collected from a representative river catchment (Kani River catchment in Gifu, Japan). The content of organic matter (OM) and its release potential to water differed obviously with type of soil origin, in the following order: vegetable field (VF) < paddy field (PF) < broadleaf forest (BF) < coniferous forest (CF) and VF < PF < CF < BF, respectively. For the released NOM, SUVA under different pH conditions decreased in the following order: neutral condition [3.6-24.0 m-1/(mg/L)] > basic condition [3.5-8.0 m-1/(mg/L)] > acidic condition [2.5-3.0 m-1/(mg/L)]. Humic acids (P1), fulvic acids (P2) and protein-like substances (P3) were the main components of the NOM released under neutral condition. The proportion of P1 and P2 released from the forest soils was lower than that from the agricultural soils. Marked differences in UV-absorbing constituents of NOM between forest and agricultural soils were found in the peak with a molecular weight of about 9800 g/mol identified as PSS (polystyrene sulfonate).